Studi Literatur: Kualitas Hidup Anak Usia Sekolah dengan Thalasemia - Fauziah, Riska; Murtiningsih, Murtiningsih; Inayah, Iin (Mando Care Jurnal, 2023)
Thalassemia major is a hematological single gene disorder that is inherited and can cause anemia in affected children, the impact of which in the world is a major public concern in Southeast Asia, including Indonesia. Indonesia is one of the countries in the thalassemia belt. In Indonesia, thalassemia major is more common and a serious health problem; about 3 – 10% of people carry the thalassemia gene due to abnormal hemoglobin production. More frequent visits to the hospital have a negative impact on children's lives in terms of physical burden, psychological burden and scholastic performance. The method used in this study is Literature review, method journal search using PICOT description and journal selection using Prism Diagram. Results of literature study in this study, the outcome as measured by PedsQL was quality of life. Questions were categorized into 4 domains: physical health, emotional health, family function and support and school and career functioning. In this study, we found that the HRQoL scores of TDT patients were higher in all dimensions compared to scores of similar studies. According to the results of several studies conducted, using the PedQL 4.0 instrument in pediatric and adolescent patients, either by distributing the instrument or by good interview technique. to patients and parents resulted in patients having a higher HRQoL in the psychosocial domain and the lowest in the education domain. This low value can be related to frequent visits to the hospital for blood transfusions or iron chelation therapy treatment so that children cannot go to school because of their perceived weakness and do not have sufficient energy to participate in school activities. So that children who do not go to school experience cognitive decline which has a negative impact on their quality of life.